Aspects of Healthcare Staffing With Specialists in Healthcare Organization and Public Health in Moscow - V. N. Tregubov; D. D. Shestakov (Здоровье мегаполиса, 2023)
Introduction. How many public health and healthcare organization professionals a health facility has on staff has a significant impact on the integration of all functional units, the ability to successfully address pressing issues, and the quality and safety of medical care.Purpose. The goal was to conduct a comparative analysis of staffing dynamics in health facilities with public health specialists in Moscow and Russia from 2017 to 2021.Materials and methods. Statistical, logical, and analytical methods were used. Data on the number of public health specialists in Moscow and Russia, workforce density and quantity of health facilities were obtained from statistical data of the Central Research Institute of Organization and Informatization of Healthcare of the Ministry of Health of the Russian Federation from 2017 to 2021. The demand for chief physicians, deputy chief physicians, methodologists, and medical statisticians was identified based on job vacancies on job search websites (HeadHunter (hh.ru), SuperJob.ru, zarplata.ru, careerist.ru) at the beginning of 2023.Result. It was shown that there remained a negative trend in Moscow, Russia, between 2017 and 2021 in the number of heads of medical organizations and their deputies. Conversely, over the five-year period the number of methodologists have increased, and the number of medical statisticians remained virtually the same. There are open positions for experts in healthcare organization and public health in the Moscow healthcare system, despite the established network of academic and educational institutions for the training of medical specialists.